From Limbo // 250 words - Villanueva, Martin V (Archīum Ateneo, 2019)
10 pages of my own poetry were featured in this international anthology. The book is described as follows on the publisher's website: A dynamic cross-cultural collection of innovative writing from the Asia-Pacific region "In the outer suburbs of Perth; Australia; a seven-year-old discovers ballroom dancing. In Jakarta; Indonesia; a poet tries to move on with his life after splitting up with his boyfriend. In the Philippines, Quezon City; a nurse reflects on her late mother while caring for a dying woman. And in the Uva province of Sri Lanka; a thirty-panel mural tells the story of a boy who refuses to speak a word."This vibrant collection features writers who have forged connections across cultures and generations; with contributors from Australia; Papua New Guinea; South Korea; Vietnam; and China; among others. Through sharing perspectives and ideas in the Writers Immersion and Cultural Exchange program; they have created exciting new work that reveals the value of genuine dialogue and mutual respect. "Spanning fiction; nonfiction; and poetry from the Asia-Pacific's finest writers, including Christos Tsiolkas; Alice Pung; Norman Erikson Pasaribu; Han Yujoo; Ellen van Neerven; and Ali Cobby Eckermann, The Near and The Far; Volume II invites readers on a unique and unforgettable journey."